The Comprehensive Aspects of Midday Meal (MDMS) on Primary School Students - Sharma, Dr. Jaya (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
It is thought that education is central to economic development, which increases productivity and living standards. Primary education is considered essential in Kerala and requires universal primary education. Mid- day meal is one of the most important policies and the main goal of education is to increase the return on education by improving the diet for children to reduce training costs and promote learning. This study showed that this plan does not contribute to improving the nutritional status of LP schools selected by both schools. Moreover, the lunch meal plan had no significant effect on the nutritional status, student enrollment and dropout. Therefore a higher caloric content of food can have a positive influence on the nutritional status of the student. The government must adjust the timing of food and food supply again. Nutritional aspects of children play a greater role in physical and mental development. Keyword: Intermediate day - Meal plan, food level, enrollment percentage, drop-out percentage, elementary students.